Perceived Readiness To Distance Learning And Digital Divide Among Selected Philippine Public Elementary Schools - Lilia Pombo Capangpangan (Fakultas Ilmu Sosial dan Ilmu Pendidikan Universitas Tadulako, 2021)
The shift from the traditional instructional materials to a digital and more inclusive platform to education, will require educators to prepare for the massive transformation of the present curriculum. Hence, an investigation was conducted to examine the readiness to distance learning modalities, and factors associated with digital divides among 15 teachers in Nena Elementary School. The data was collected using a three-part survey questionnaire, and were analyzed via descriptive and inferential statistics with respect to the .05 threshold of significance. Findings revealed that the availability of teaching tools significantly predicts the increase of teachers’ readiness on the delivery of instruction via distance learning modalities. Due to this, the researcher recommends among curriculum chief persons to look for ways to aid teachers in ensuring the availability of teaching tools appropriate in the digitalization of education in the new normal.